International survey on the perioperative management of pulmonary endarterectomy: the perfusion perspective. (January 2018) - Stanzel, Roger D.P.; Gehron, Johannes; Wolff, Matthias; Striegl, Natalie; Roth, Peter; Boedeker, Rolf-Hasso; Scheibelhut, Christine; Herrmann, Johannes; Welters, Ingeborg; Mayer, Eckhard; Scheffler, Matthias
Introduction: Pulmonary endarterectomy (PEA) is the most effective treatment available for chronic thromboembolic pulmonary hypertension (CTEPH). Patient selection, surgical technique and perioperative management have improved patient outcomes, which are traditionally linked to surgical and center experience. However, optimal perfusion care has not been well defined. The goal of the international survey was to better characterize the contemporary perfusion management of PEA and highlight similarities and controversies. Method: The combined caseload of 15 participating centers was 5, 066 cases. Topics queried included materials and types of cardiopulmonary bypass (CPB) equipment, choice of prime, fluid management, deep hypothermia strategy, temperature management, treatment of acid-base abnormalities and intraoperative hematocrit as well as anticoagulation management for heparin-induced thrombocytopenia. Conclusion: Our assessment could provide a base for further advancement and may help design future studies to elucidate the impact of perfusion in this challenging field.